Manipulation in mass media - Shymanovska Yuliana (My University, 2020)
The aim of this thesis is to specify and reveal main manipulation strategies used in mass media. To accomplish this aim the following objectives were set: - analyze available research findings concerning linguistic and extra-linguistic means of the mass media manipulation; - compare the most effective tools of manipulation used in mass media; - analyze the depiction of beauty in women’s magazines and the portrayal of the beauty standards in the context of mass media; - reveal how mass media manipulate the body image.